2020
DOI: 10.1097/jxx.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of disaster management knowledge and skills among advanced practice registered nurses

Abstract: Background and purpose: Disaster management experts around the world agree that nurses play a vital role in disaster preparation, response, and recovery. The Joint Commission on Accreditation of Health care Organizations requires biannual disaster drills for accredited facilities, and there are numerous training resources and educational materials on disaster management topics. Multiple federal and state laws govern health care provider activities during a disaster. However, there is a lack of guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, their intended purpose was not to train course members in their profession or area of specialisation (that is, instructing nurses in nursing or logisticians in logistics) but, rather, education in the specific elements of disaster management [10]. However, this proposal contradicts the general perception of doctors and nurses about their deficit in technical competence in the context of disaster management [16][17][18][19][20], a perception that arises from the lack of undergraduate degree training in subjects related to emergencies at most European universities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their intended purpose was not to train course members in their profession or area of specialisation (that is, instructing nurses in nursing or logisticians in logistics) but, rather, education in the specific elements of disaster management [10]. However, this proposal contradicts the general perception of doctors and nurses about their deficit in technical competence in the context of disaster management [16][17][18][19][20], a perception that arises from the lack of undergraduate degree training in subjects related to emergencies at most European universities.…”
Section: Discussionmentioning
confidence: 99%
“…Without contradicting the global approach taken by the DITAC project, the 2015–30 Sendai Framework places human health at the centre of disaster management and considers the development of healthcare personnel in this area a vital issue [ 6 ]. However, since then, several publications have shown that the technical (knowledge) and methodological (know-how) skills of doctors and nurses remain insufficient in this field [ 9 , 13 , 16 , 17 , 18 , 19 , 20 ]. Despite the efforts made to standardise EPDMs over the last 7 years, we still do not know whether the European EPDMs aimed at health professionals have incorporated the evidence-based recommendations that standardised curricula should be developed to deal with the challenges posed by disasters.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, both the intervention and control groups received disaster nursing knowledge and skills training. The scores of the two groups were significantly higher than in the pretest, indicating that training can improve the disaster skills of nurses [ 24 ]. The United States began to provide disaster preparedness education for nurses at 2001, while disaster education for nurses in China began after the Wenchuan Earthquake in 2008 [ 25 ].…”
Section: Discoursementioning
confidence: 99%
“…Prior to the study, the concept of Advanced Clinical Practitioners dealing with uncertainty was under explored and this provided the impetus for research into this crucial area during the COVID-19 pandemic. Currently, there is a lack of guidance on the specific role responsibility for Advanced Clinical Practitioners in situations that are unpredictable with a strong suggestion that many are ill-prepared in the management of disasters ( Fil et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%